2017
DOI: 10.1080/17482798.2017.1365737
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the association between children’s screen media exposure and vocabulary size in the UK

Abstract: Children are growing up in a digital age with increasing exposure to television and touchscreen devices. We tested whether exposure to screen media is associated with children's early language development. One hundred and thirty-one highly educated caregivers of UK children aged 6-36 months completed a media exposure questionnaire and vocabulary measure. 99% of children were read to daily, 82% watched television, and 49% used mobile touchscreen devices daily. Regression analyses revealed that time spent readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 42 publications
2
45
1
Order By: Relevance
“…Vatalaro et al ( 2018 ) demonstrated the benefits of using a scaffolding-like vocabulary application rather than any open-ended vocabulary application. Taylor et al ( 2018 ) suggest that teaching and reading activities act as a beneficial agent for learning. These authors also devalue the screen time where they did not find benefits or damages in their use.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Vatalaro et al ( 2018 ) demonstrated the benefits of using a scaffolding-like vocabulary application rather than any open-ended vocabulary application. Taylor et al ( 2018 ) suggest that teaching and reading activities act as a beneficial agent for learning. These authors also devalue the screen time where they did not find benefits or damages in their use.…”
Section: Discussionmentioning
confidence: 99%
“…The third limitation of some studies is the selected methodology and the causality inference, by the use of observational and cross-sectorial studies instead of experimental and longitudinal methods (Mendelsohn et al, 2010 ; Papadakis et al, 2018 ; Tansriratanawong et al, 2017 ; Taylor et al, 2018 ; Tomopoulos et al, 2007 ; Vatalaro et al, 2018 ; Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations